2015
DOI: 10.1002/suco.201400042
|View full text |Cite
|
Sign up to set email alerts
|

Design of composite slabs with prepressed embossments using small‐scale tests

Abstract: The load bearing capacity of steel and concrete composite slabs using thin-walled steel sheeting with prepressed embossments is in most cases determined by its resistance in longitudinal shear. The designing of composite slabs still requires the performance of full-scale laboratory bending tests. Small-scale shear tests cannot include all of the influences affecting the bended slab but using an appropriate procedure the shear characteristics obtained from them can be used for determining the bending capacity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…For the last specimen with a span length of 1300 mm, τu,Rd equals 0.328 N/mm². The ultimate resistance of ferritic stainless steel slabs calculated herein and in [2,18] is similar to the resistance of slabs made of galvanized steel [20] and always higher than the nominal resistance of galvanized steel slabs [19].…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…For the last specimen with a span length of 1300 mm, τu,Rd equals 0.328 N/mm². The ultimate resistance of ferritic stainless steel slabs calculated herein and in [2,18] is similar to the resistance of slabs made of galvanized steel [20] and always higher than the nominal resistance of galvanized steel slabs [19].…”
Section: Resultssupporting
confidence: 56%
“…Besides, in [20], galvanized steel Cofraplus 60 composite slabs were tested. Several differences exist between their specimens and the current ones: the sheet thickness equaled 1.0 mm, the total height was 110 mm, C20/25 concrete was used and no crack inducers were included.…”
Section: Psc Diagrammentioning
confidence: 99%
See 1 more Smart Citation
“…For the last specimen with a span length of 1300 mm, τu,Rd equals 0.328 N/mm². The ultimate resistance of ferritic stainless steel slabs calculated herein and in [2,18] is similar to the resistance of slabs made of galvanized steel [20] and always higher than the nominal resistance of galvanized steel slabs [19]. It is therefore concluded that the stainless steel corrugated sheet and the concrete behave as a single structural component and should be considered as such in the design of composite slabs.…”
Section: Resultssupporting
confidence: 64%
“…Nevertheless, the bending effect was not adequately performed, due to the specimen's small length and the test equipment's nature. Moreover, specimen handling and storage issues were challenging [53].…”
Section: Introductionmentioning
confidence: 99%